Gordon: Using Flash Memory to Build Fast, Power-efficient Clusters for Data-Intensive Applications - Caulfield, Adrian; Grupp, Laura M.; Swanson, Steven (ASPLOS '09: Proceeding of the 14th international conference on Architectural support for programming languages and operating systems, 2009)
As our society becomes more information-driven, we have begun to amass data at an astounding and accelerating rate. At the same time, power concerns have made it difﬁcult to bring the necessary processing power to bear on querying, processing, and understanding this data. We describe Gordon, a system architecture for data-centric applications that combines low-power processors, ﬂash memory, and datacentric programming systems to improve performance for data-centric applications while reducing power consumption. The paper presents an exhaustive analysis of the design space of Gordon systems, focusing on the trade-offs between power, energy, and performance that Gordon must make. It analyzes the impact of ﬂash-storage and the Gordon architecture on the performance and power efﬁciency of data-centric applications. It also describes a novel ﬂash translation layer tailored to data-intensive workloads and large ﬂash storage arrays. Our data show that, using technologies available in the near future, Gordon systems can out-perform disk-based clusters by 1.5× and deliver up to 2.5× more performance per watt.
Selected as an IEEE Micro TopPick